Evaluation of the Implementation of Precision Agricultural Technology on Tidal Land: Case Study in Tanjung Baru Village, Muara Padang, Banyuasin Regency, South Sumatra of Indonesia - Rahim, Supli; Aminah, Raden Iin Siti; Marlina, Neni; Batubara, Mustopa Marli; Murtado, Ade; Helida, Asvic; Basuki, Rahmad; Elfama, Yudha; Rosita; Fitriani; Natalia, Anita; Yusup, Muhammad; Lucyana; Saputra, Ari; Fitriani, Eka Yuliana; Sapsidi, Herlianto; Permana, Deddy; Badriah, Dina; Damiri, Nurhayati; Supli, Nur Aslamiah (Journal of Smart Agriculture and Environmental Technology, 2025)
The study aims to evaluate the application of precision farming  technology in Tidal Land, Tanjung Baru Village, Muara Padang, Banyuasin. The study uses quantitative and qualitative approaches with field observation and survey methods and in-depth interviews. The population of the study was all farmers who manage agricultural land in Tanjung Baru Village. The research sample was taken purposively, namely farmers who have implemented or tried to implement precision farming. The number of samples was 30 farmers. Data collected included the use of precision farming technology, the obstacles faced and its impact on farmer productivity and welfare. In addition, the experience of farmers in implementing precision farming and identifying proposed solutions was also studied. Results of this study are that the majority of farmers in Tanjung Baru Muara Padang Banyuasin village were aged 41-50 years (46.7 percent), with an even level of education between high school, junior high school, and elementary school graduates. The largest land ownership is 3-5 hectares (53.3 percent). As many as 93.3 percent of respondents have implemented precision farming technology, with tractors and combine harvesters as the most commonly used technology. GIS  technology is used by 23.3 percent of respondents, drones by 10 percent, and plowing tools and machines and GRPS systems by 3.3 percent of respondents each. The main reasons for using technology are to increase farming productivity, reduce costs, and increase farming efficiency. Respondents want easy access to technology (50 percent), technical assistance (26.7 percent), and subsidy and financial assistance (20 percent). As many as 90 percent of respondents stated that they would continue to use precision farming technology in the future. More than 30 percent of respondents suggested assistance with precision farming tools and education and training, while 20 percent suggested the provision of water pumps. This indicates the need for comprehensive and sustainable support to increase the adoption of precision farming technologies.